Translator's handbook on Paul's letter to the Romans. - Newman, Barclay M.; Nida, Eugene Albert, 1914- (London, UK United Bible Societies, 1973)
Includes bibliographbical references and indexes.
Keywords: Bible. N.T. Romans -- study and teaching